An assessment of the Blue Economy in Namibia: a case study of Swakopmund and Walvis Bay - Mouton, Sophia Florence (Graduate School of Business (GSB), 2019)
The main thrust of this research was to assess the Namibia blue economy: a case study of Walvis Bay and Swakopmund. The research was aimed at identifying how the government can achieve inclusive growth while at the same time ensuring that there is sustainable resource management. A qualitative research design was then adopted, with the target population of the study being the Ministry of Fisheries and Marine Resources employees, and previously disadvantaged people in Namibia. A purposive sampling technique was used to select the Ministry of Fisheries employees, and a random sampling technique was adopted to reach the 40 previously disadvantaged people. The research revealed that the Namibian blue economy is not currently sustainably utilised, due to policy incoherence and weak enforcement of the Namibianisation policy. These findings establish the need for participatory policy design and implementation to develop community, which is crucial for the sustainability of the blue economy. The results also revealed the lack of multi-sector partnerships, thus effectively limiting the benefits that could be harnessed from the Namibian blue economy. If Namibia were to set up all the necessary institutions and build the relevant capacities, it would enjoy the benefits of resource efficiency, sustainable business operations, inclusive jobs and improved well-being.